The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1073/pnas.0908134107
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association identifies candidate genes that influence the human electroencephalogram

Abstract: Complex psychiatric disorders are resistant to whole-genome analysis due to genetic and etiological heterogeneity. Variation in resting electroencephalogram (EEG) is associated with common, complex psychiatric diseases including alcoholism, schizophrenia, and anxiety disorders, although not diagnostic for any of them. EEG traits for an individual are stable, variable between individuals, and moderately to highly heritable. Such intermediate phenotypes appear to be closer to underlying molecular processes than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 49 publications
6
83
1
1
Order By: Relevance
“…The effects of variants may be context-dependent, leading to failures to detect loci in the absence of exposure, or in the presence of exposures that overwhelm the effects of genes [125]. The use of intermediate phenotypes that are less subject to environmental perturbation and closer to the function of molecular networks appears to amplify power of GWA [126]. If, despite the lack of evidence from transmission studies, 'epistasis is the rule', it may be necessary to test combinations of common alleles [127].…”
Section: Methodologies For Gene Discoverymentioning
confidence: 99%
“…The effects of variants may be context-dependent, leading to failures to detect loci in the absence of exposure, or in the presence of exposures that overwhelm the effects of genes [125]. The use of intermediate phenotypes that are less subject to environmental perturbation and closer to the function of molecular networks appears to amplify power of GWA [126]. If, despite the lack of evidence from transmission studies, 'epistasis is the rule', it may be necessary to test combinations of common alleles [127].…”
Section: Methodologies For Gene Discoverymentioning
confidence: 99%
“…Однако стоит отме-тить, что ассоциация была продемонстрирована только для двух из трех проанализированных выборок. В полногеномном исследовании (Hodgkinson et al, 2010) на выборке 322 американских индейцев найдена связь однонуклеотидных полиморфизмов в гене SGIP1 (SH3-domain GRB2-like endophilin-interacting protein 1) с мощностью тета-диапазона ЭЭГ.…”
Section: генетически информативные исследования функциональной активнunclassified
“…Other studies have determined that the human electroencephalogram is influenced by the genome and also by a significant number of gene types (SGIP1, ST6GAL-NAC3, and UGDH) [22]. Moreover, it has been shown that specific hereditary genes such as BRCA1 and BRCA2 and proteins such as 14-3-3 [24] affect neuronal reactivity [22,25]. Genetic studies have demonstrated that the aforementioned genes and proteins are associated directly with two types of breast cancer [26][27][28][29]: hereditary and non-hereditary.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies some brain activities recorded via EEG have been shown to be associated with particular genes and proteins [22] that play a crucial role in the normal (or, conversely, the abnormal) development of breast cells [23]. Other studies have determined that the human electroencephalogram is influenced by the genome and also by a significant number of gene types (SGIP1, ST6GAL-NAC3, and UGDH) [22]. Moreover, it has been shown that specific hereditary genes such as BRCA1 and BRCA2 and proteins such as 14-3-3 [24] affect neuronal reactivity [22,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation